The LTE/SAE deployment handbook - Penttinen, Jyrki T. J. (Chichester, West Sussex ; Hoboken, NJ, 2012)
'Comprehensively covers the planning, rolling out and optimization of LTE/SAE networks. A hands-on description of the complete end-to-end functionality, network planning and physical construction of LTE networks, The LTE/SAE Deployment Handbook: The Functioning, Measurements and Planning of Evolved Packet System is unique in its practical approach to the topic. This book gives a complete picture of LTE systems, as well as providing many examples from the operational networks, in order to be used as a handbook and guide in the planning and operational phase of the networks.Describing the principles and details of LTE/SAE, with a complete view on the functioning, planning, construction, measurements and optimisation of the radio and core networks of the system, it also focuses on the practical description of LTE/SAE, how to de-mystify the LTE functionality and planning and carry out practical measurements of the system. The contents include a general view (the evolution path, network architecture and business models), technical functioning of the system (signalling, coding, different modes for channel delivery and security of core and radio system) and information on the in-depth planning of the core and radio networks (field test measurement guidelines, hands-on network planning advices and suggestions for the parameter adjustments). It also describes the next generation of LTE, LTE-Advanced, which represents the initial fourth generation of the mobile systems.The book contains a preliminary module that is suitable as an introduction to the more advanced level of the topic, including the initial studies and revisions of the technical and marketing aspects. The latter part of the book is designed for more experienced professionals who would benefit from the practical descriptions of the physical core and radio network planning, end-to-end performance measurements, physical network construction and optimisation of the system'--
'This book gives a complete picture of LTE systems, as well as providing many examples from the operational networks, in order to be used as a handbook and guide in the planning and operational phase of the networks'--
Includes bibliographical references and index.
Keywords: Long-Term Evolution (Telecommunications); System Architecture Evolution (Telecommunications); TECHNOLOGY & ENGINEERING / Mobile & Wireless Communications